Gallbladder Duplication Associated with Gastro-Intestinal Atresia - Rahul Gupta; Shilpi Gupta; Pramila Sharma; Anu Bhandari; Arun Kumar Gupta; Praveen Mathur (EL-Med-Pub, 2016)
Gallbladder duplication in association with other GIT anomalies is a rare entity. We report two neonates; one with duodenal atresia and the other newborn with pyloric atresia, ileal atresia and colonic atresia, both were associated with gallbladder duplication which has not been reported earlier.